More inclusive bipolar mixed depression definition by permitting overlapping and non‐overlapping mood elevation symptoms. (2nd May 2016) - Kim, H.; Kim, W.; Citrome, L.; Akiskal, H. S.; Goffin, K. C.; Miller, S.; Holtzman, J. N.; Hooshmand, F.; Wang, P. W.; Hill, S. J.; Ketter, T. A.
Abstract : Objective: The objective of this study was to assess the strengths and limitations of a mixed bipolar depression definition made more inclusive than that of the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM‐5) by counting not only 'non‐overlapping' mood elevation symptoms (NOMES) as in DSM‐5, but also 'overlapping' mood elevation symptoms (OMES, psychomotor agitation, distractibility, and irritability). Methods: Among bipolar disorder (BD) out‐patients assessed with the Systematic Treatment Enhancement Program for BD (STEP‐BD) Affective Disorders Evaluation, we assessed prevalence, demographics, and clinical correlates of mixed vs. pure depression, using more inclusive (≥3 NOMES/OMES) and less inclusive DSM‐5 (≥3 NOMES) definitions. Results: Among 153 depressed BD, counting not only NOMES but also OMES yielded a three‐fold higher mixed depression rate (22.9% vs. 7.2%) and important statistically significant clinical correlates for mixed compared to pure depression (more lifetime anxiety disorder comorbidity, more current irritability, and less current antidepressant use), which were not significant using the DSM‐5 threshold. Conclusion: To conclude, further studies with larger numbers of patients with DSM‐5 bipolar mixed depression assessing strengths and limitations of more inclusive mixed depression definitions are warranted, including efforts to ascertain whether or not OMES should count toward mixed depression.